Changing Preferences with Ageing – Housing Choices and Housing Plans of Older People. Issue 2 (2nd April 2016) - Abramsson, Marianne; Andersson, Eva
Abstract: Planning for the housing situation of an ageing population is one of the challenges of many countries. To increase our understanding of the needs of the ageing population, a nationwide survey stratified on age and municipality type was conducted. Research questions referred to the current housing situation and plans. The aim was to investigate how preferences, location, and/or the type of housing preferred changes with age and if they are housing market dependent. Results of 10-year cohorts show that the most marked change is between the cohort 75–84 years old and the oldest cohort 85+. There is a gradual change over time of moves from large to small housing, from owner-occupation to rented housing. Respondents in the major cities and in the rural or tourism-dependent municipalities are less inclined to move compared to those from other types of municipalities. The study predicts a shortage of rented apartments.